KINETIKA PENGERINGAN SARI BUAH MENGKUDU DENGAN METODE FOAM MATE DRYING - Muhammad Iqbal Nusa (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
The objective of this reasearch to study the effect of concentration egg albumin as foam agent, and duration of time whipping to physical caracteristic foam of the mengkudu fruit juice,and kinetic of foam mate drying. The stage of the reasearch have compiled to obtain juice mengkudu fruit by mechanical extraction. To adding maltodextrin (foaming stability) 5% (w/w), egg albumin (foaming agent) as the first factor four level as 0,25 %; 5 %; 7,5 %; and 10 % (w/w). Foaming process by whipping as the second factor with four level of duration time whipping 5; 10; 15; and 20 minute. Quality of foaming indicators were cracteristic foaming as foaming expansion and density of foaming. And then foaming material to dry with foam mate thin drying methode at 700C to equilibrium moisture content. Measurement of paramater were characteristic physical of foaming, alteration of moisture content, the rate of drying, difusivitas moisture, and moisture content. The result of reasearch data have indicated the corelation increasing of foaming expansion with adding egg albumin concentration and prolong duration time of whipping, increasing of rate of drying and number of difusivitas moisture foam mate drying.